Analisis Kepuasan Pengguna Terhadap Tokopedia Menggunakan Metode Service Quality (Servqual) - Rukmantara, Muhammad Rakha Adrian; Hertyana, Hylenarti; Hernawati (Jurnal INSAN Journal of Information System Management Innovation, 2025)
The development of information and communication technology has transformed business practices in Indonesia, with e-commerce platforms like Tokopedia playing a crucial role in the digital ecosystem. However, Tokopedia users face challenges such as delayed responses and product description mismatches that impact user satisfaction. This study aims to analyze Tokopedia user satisfaction using the SERVQUAL method encompassing five dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The problem is addressed by identifying gaps between user expectations and perceptions of Tokopedia's service quality through SERVQUAL GAP analysis, then providing improvement recommendations based on priority dimensions with the highest negative GAP values. The research employed a descriptive quantitative approach with 100 Tokopedia users selected using the Lemeshow formula. Data was collected through online questionnaires distributed via Discord platform and analyzed using SERVQUAL GAP analysis method. Validity test results showed all question items were valid (r calculated > 0.195) and reliable (Cronbach's Alpha > 0.7). The findings revealed an average GAP value of -0.3, indicating overall user dissatisfaction with Tokopedia's services. The Tangibles dimension showed positive satisfaction (GAP 0.18), while four other dimensions indicated dissatisfaction: Empathy (-0.7), Responsiveness (-0.57), Assurance (-0.29), and Reliability (-0.12). This study provides priority improvement recommendations for Empathy and Responsiveness dimensions to enhance Tokopedia user satisfaction.